The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1530/eje-19-0570
|View full text |Cite
|
Sign up to set email alerts
|

Activity and safety of temozolomide in advanced adrenocortical carcinoma patients

Abstract: Objective Temozolomide has shown a significant anti-proliferative activity on adrenocortical cancer (ACC) cells in vitro. Design On the basis of these results the drug was prescribed as second/third line in advanced metastatic ACC patients in four referral centers in Italy. Methods We retrospectively collected anagraphic, clinical and pathological data of patients with advanced ACC with disease progression to standard chemotherapy plus mitotane who were treated with temozolomide at the dose of 200 mg/m2/di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Twenty-three of them (46.9%) were on adjuvant mitotane therapy [5]. Among the 43 patients with metastatic disease, 25 (58.1%) were treated with mitotane, 18 (41.8%) were receiving chemotherapy + mitotane as follows: first line EDP (Etoposide, Doxorubicin, Cisplatin) [6] in 8 patients; second/third line therapies with temozolomide [7] in 5 patients (4%) and gemcitabine-capecitabine [8] in 5 patients (5%). Forty-seven patients (51.1%) were resident in Lombardy while the remaining 45 lived in the rest of Italy.Six ACC patients (6.5%) developed COVID-19 symptoms, five of them resident in Lombardy.…”
mentioning
confidence: 99%
“…Twenty-three of them (46.9%) were on adjuvant mitotane therapy [5]. Among the 43 patients with metastatic disease, 25 (58.1%) were treated with mitotane, 18 (41.8%) were receiving chemotherapy + mitotane as follows: first line EDP (Etoposide, Doxorubicin, Cisplatin) [6] in 8 patients; second/third line therapies with temozolomide [7] in 5 patients (4%) and gemcitabine-capecitabine [8] in 5 patients (5%). Forty-seven patients (51.1%) were resident in Lombardy while the remaining 45 lived in the rest of Italy.Six ACC patients (6.5%) developed COVID-19 symptoms, five of them resident in Lombardy.…”
mentioning
confidence: 99%
“…DNA alkylation appears to be a critical point for inducing cytotoxicity in the ACC; indeed, cisplatin is a fundamental component of the EDP-M scheme. Furthermore, results obtained both in vitro [9] and in vivo [10] support the antineoplastic activity of another alkylating agent such as temozolomide against ACC. Trabectedin (ET-743) is a powerful anti-tumor drug isolated from the Caribbean tunicate Ecteinascidia turbinata.…”
Section: Introductionmentioning
confidence: 55%
“…In a recently conducted retrospective study, single agent temozolomide was found active as second line approach in advanced ACC patients with a response rate observed in 20% of patients. The disease control rate obtained, however, was short-lived (10).…”
mentioning
confidence: 87%